Effects of levamisole on hyaluronidase activity and sperm characteristics in rams - Bozkurt, T; Tanyıldızı, S; Türk, G (My University, 2004)
The aim of this study was to determine the effects of levamisole on sperm characteristics and hyaluronidase activity of blood serum and semen. For this purpose, 12 Akkaraman rams (2–3 years old) were used. Levamisole hydrochloride was administered orally at a dose of 7.5 mg/kg body weights once daily for 2 days. Serum and semen samples were collected from the rams at posttreatment 1, 2, 4, 24, 48, 72, 96, 120, 144, 216, 288 and 384 h and examined for sperm characteristics and hyaluronidase activity. The results showed that the use of levamisole caused significant (P < 0:01) increase in serum hyaluronidase activity at all times except the 72 h, and in semen hyaluronidase activity at 1, 2, 4, 24, 72, 96 and 120 h compared to the control group. In addition, the levamisole caused significant (P < 0:05) decreases in semen volume, sperm motility, concentration and total sperm number at all times. There was no correlation between semen hyaluronidase activity and the sperm characteristics. In conclusion, levamisole did not have any deleterious effect on hyaluronidase enzyme. However, the use of this drug in rams during the breeding season is harmful due to the decrease of sperm characteristics.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: levamisole; sperm; ram